Analisis Efektivitas Project-based Learning Dalam Meningkatkan Keterampilan Berpikir Kritis Siswa - Irfan (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the effectiveness of Project-based Learning (PjBL) in improving students' critical thinking skills. The method used is a narrative review study, which examines various studies related to the impact of PjBL on critical thinking skills at various levels of education. A literature search was conducted using keywords such as